Impact of Extension Interventions on Capacity Building of Tribal Backyard Poultry Owners in Kandhamal District of Odisha - D. V. Singh, P. N. Jagdev and M. R. Mohapatra, (Indian Journal of Extension Education, 2018)
The study investigates the impact of extension interventions on capacity building of tribal backyard poultry owners in randomly selected six villages of G. Udayagiri and K. Nuagoan blocks of Kandhamal district of Odisha by Random proportionate sampling (RPS) method. Data were collected through a structured interview schedule from 60 respondent's (30 from each block) tribal poultry owners by personal interview method and they were analysed using percentage frequency and chi-square. Suitable extension interventions like group discussion, awareness cum animal health treatment camps, exposure visits, training programmers were applied in the study areas. The capacity building of poultry owners were measured on the basis of improvement in knowledge and change in attitude towards scientific poultry farming practices. The chi-square test was applied 'before' and 'after' interventions of various extension strategies. The study showed a significant improvement in the knowledge and attitude of tribal poultry owners after extension interventions. It concluded that the capacity building of poultry owners were increased on the basis of improvement in knowledge and scientific farming practices